A Path Model of Factors Associated with Hypertension and Disease: Analysis of Indonesian Basic Health Survey Year 2018 - Didik HARIYADI; Widyana Lakshmi Puspita; Taufik ANWAR; Slamet WARDOYO (Modern Medicine)
Non-communicable diseases are estimated to account for 73% of all deaths in Indonesia, and cardiovascular disease contributes 35%. Unhealthy dietary behavior leads to several NCDs, such as Diabetes Mellitus, obesity, hypertension, cardiovascular disease, and stroke. This cross-sectional study used secondary data from the Indonesian Basic Health Survey Year 2018. The study selected 10,171 samples aged ≥15 years from West Borneo Province. The dependent variable was coronary disease. The independent variables were hypertension, age, gender, education, smoking, vegetables, fruit consumption, fat intake, alcohol consumption, instant noodles consumption, soft drink consumption, physical activity, and residence. A path analysis was conducted data analysis. The coronary disease was directly increased by hypertension (b=1.19; 95% CI=0.90 to 1.48; p<0.001), age ≥43 years (b=0.88; 95% CI=0.55 to 1.21; p<0.001), and high physical activity (b= -0.49; 95% CI= -0.81 to -0.17; p=0.003). It was directly decreased by alcohol consumption, but it was statistically non-significant (b=-0.71; 95% CI=-1.54 to 0.11; p=0.088). Coronary disease was indirectly affected by males, smoking, vegetable consumption, fruit consumption, fat intake, grilled food consumption, energy drink consumption, instant noodles consumption, soft drink consumption, residence, and education.